Role of CYP2C9, CYP2C19 and EPHX Polymorphism in the Pharmacokinetic of Phenytoin: A Study on Uruguayan Caucasian Subjects - Natalia Guevara; Cecilia Maldonado; Manuel Uría; Raquel González; Manuel Ibarra; Silvana Alvariza; Antonella Carozzi; Carlos Azambuja; Pietro Fagiolino; Marta Vázquez (MDPI AG, 2017)
Phenytoin (PHT) oxidative route leads to its main metabolite p-hydroxyphenytoin (p-HPPH), by means of CYP2C9 and CYP2C19. Formation of p-HPPH proceeds via a reactive arene-oxide intermediate. This intermediate can also be converted into PHT dihydrodiol by microsomal epoxide hydrolase (EPHX). The three enzymes are polymorphically expressed and the genetic variants are responsible for changes in the enzyme activity. In order to evaluate the effect that these polymorphisms have on PHT metabolism, PHT and p-HPPH plasma concentrations were measured and the genotype for the three enzymes was assessed in 50 Uruguayan epileptic patients. 30% of the patients were intermediate and 2% were poor metabolizers for CYP2C9, while 20% were intermediate metabolizers for CYP2C19. 44%, 10%, and 46% of subjects had intermediate, increased and decreased activities of EPHX respectively. CYP2C9 was confirmed to be the main responsible enzyme for PHT biotransformation. CYP2C19 seemed to be preponderant in p-HPPH oxidative metabolism. Apart from being responsible for the production of the dihydrodiol metabolite, EPHX also seemed to contribute to pHPPH formation when its activity is low. PHT might be recovered with a decreased activity of EPHX regardless the activity of CYP2C9.